A Hormone That Lost Its Receptor: Anti-Müllerian Hormone (AMH) in Zebrafish Gonad Development and Sex Determination. Issue 2 (1st October 2019) - Yan, Yi-Lin; Batzel, Peter; Titus, Tom; Sydes, Jason; Desvignes, Thomas; BreMiller, Ruth; Draper, Bruce; Postlethwait, John H
Abstract: Anti-Mullerian hormone (Amh) inhibits female reproductive duct development, signals oocyte reserve, and marks polycystic ovarian syndrome. Zebrafish lacks Mullerian ducts and the typical Amh receptor, questioning evolving roles of Amh. Yan et al. made knockout mutations in zebrafish... Fetal mammalian testes secrete Anti-Müllerian hormone (Amh), which inhibits female reproductive tract (Müllerian duct) development. Amh also derives from mature mammalian ovarian follicles, which marks oocyte reserve and characterizes polycystic ovarian syndrome. Zebrafish ( Danio rerio ) lacks Müllerian ducts and the Amh receptor gene amhr2 but, curiously, retains amh . To discover the roles of Amh in the absence of Müllerian ducts and the ancestral receptor gene, we made amh null alleles in zebrafish. Results showed that normal amh prevents female-biased sex ratios. Adult male amh mutants had enormous testes, half of which contained immature oocytes, demonstrating that Amh regulates male germ cell accumulation and inhibits oocyte development or survival. Mutant males formed sperm ducts and some produced a few offspring. Young female mutants laid a few fertile eggs, so they also had functional sex ducts. Older amh mutants accumulated nonvitellogenic follicles in exceedingly large but sterile ovaries, showing that Amh helps control ovarian follicle maturation and proliferation. RNA-sequencing data partitioned juveniles at 21 days postfertilization (dpf) into two groups that each contained mutant and wild-type fish. Group21-1 upregulated ovary genes compared to Group21-2, which were likely developing as males. By 35 dpf, transcriptomes distinguished males from females and, within each sex, mutants from wild types. In adult mutants, ovaries greatly underexpressed granulosa and theca genes, and testes underexpressed Leydig cell genes. These results show that ancestral Amh functions included development of the gonadal soma in ovaries and testes and regulation of gamete proliferation and maturation. A major gap in our understanding is the identity of the gene encoding a zebrafish Amh receptor; we show here that the loss of amhr2 is associated with the breakpoint of a chromosome rearrangement shared among cyprinid fishes.